MENGOPTIMALKAN HASIL PRESTASI BELAJAR MATA PELAJARAN FISIKA DENGAN MATERI PEMBELAJARAN GERAK LURUS MELALUI SYNETICS APPROACH - Esti Wahyuni (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2022)
The use of the Synetic Approach (an approach that focuses students' attention and competence) in the Straight Motion learning process helps learning so that it runs optimally. Students can easily understand and master the subject matter, in addition, students are required to be active, responsible and disciplined in teaching and learning activities. This study aims to improve student achievement through the application of a synectic approach. This study uses classroom action research (CAR) which was conducted at SMK SMTI Pontianak in the odd semester of the 2019/2020 academic year on Straight Motion material. The implementation of the action was carried out in three cycles and carried out in four stages, namely: planning, action, observation, and reflection. The results of the research at the first meeting of the sub-subject material for Regular Motion Learning obtained an average score of 61.15 with a completeness of 31%, then the results of reflection then in the second cycle for the sub-subject of uniformly changing straight motion obtained an average score of 68.46 with completeness 69%. In the third cycle, the sub-subject of vertical motion obtained an average score of 80.73 with 100% completeness. From physics learning that is carried out using the Synetics Approach, it is found that student learning achievement increases, then in the process of action by the teacher in learning using the Synetic Approach, it can help, develop and complete physics learning materials or materials for students so that they are trained to acquire deeper knowledge.